TANGGAP BEBERAPA KLON NILAM (Pogostemon cablin Benth.) TERHADAP NEMATODA PELUBANG AKAR (Radopholus simitis Cobb.) - YANG NURYANI; CHEPPY SYUKUR; RITA HARNI; YELNI TITIS; REPIANYO REPIANYO; IKA MUSTIKA (Pusat Penelitian dan Pengembangan Perkebunan, 1999)
Response of some patchouli clones (Pogostemon cablin Benth.) to burrowing nematode (Radopholus similis Cobb.)One of the seious poblems on patchouli is infection of plant parasitic nematode. Nine clones of Aceh patchouli (Pogostemon cablin Benth.) namely KJ (oiginated from tissue cultue) Meulaboh-2, Sidikalang, Lhokseumawe-2, Cisaroni . Cirateun, Tapak Tuan. Aceh Merah. Situak-2, and one clone of Java patchouli (P. heyneanus Benth.) namely Giilaya, were tested to infection of buowing nematode (Radopholus similis Cobb.) in the glasshouse of Research Institute for Spice and Medicinal Crops, Bogor fom July to November 1997. Each clone was inoculated with 500 of R. similis. An expeiment have been conducted to know the esponse of some patchouli cultivars against nematode. The expeiment was arranged in a Completely Randomized Design with thee replicates. The esults showed that the infection of R. similis reduced root weight greater than that of shoot weight, the colour of leaf became reddish or dark purple. Based on the development rate of nematode and level of damage, Giilaya appeared to be resistant, whereas Sidikalang, Cisaroni and Situak-2 clones wee slightly susceptible. KJ. Lhokseumawe-2, Cirateun. Tapak Tuan and Aceh Merah clones were susceptible, whereas Meulaboh-2 were highly susceptible against R. similis. Characteistic of Java clone that esistance and Aceh clone that shyhtly susceptible to R. similis may be useful for providing new vaieties with high content of oil and resistant to nematode.